An efficient inoculation method to evaluate virulence differentiation of field strains of sugarcane smut fungus - Guo, Feng; Meng, Jiaorong; Huang, Ji; Yang, Yanfang; Lu, Shan; Chen, Baoshan (Frontiers in Microbiology, 2024)
Sugarcane smut, caused by the fungal pathogen Sporisorium scitamineum, is a prominent threat to the sugarcane industry. The development of smut resistant varieties is the ultimate solution for controlling this disease, due to the lack of other efficient control methods. Artificial inoculation method is used to evaluate the virulence differentiation of pathogens. The mostly used artificial inoculation methods are soaking of the seed canes in the teliospore solution and injection of teliospores or haploid sporidia into the sugarcane sprouts. However, due to the infection nature of the pathogen that invades the sugarcane plant through meristem tissue of the sprout or shoot, the rate of successful infection is often low and fluctuated, resulting in low confidence of the assays. We recently reported a rapid and high-throughput inoculation method called plantlet soaking by using tissue culture-derived sugarcane plantlets as the test plants. Here, we compare different inoculation methods and report the characterization of parameters that may affect the sensitivity and efficiency of the plantlet soaking technique. The results showed that sugarcane plantlets were highly vulnerable to infection, even with the inoculum density at 6.0 × 10 5 basidial spores/ml, and this method could be applied to all varieties tested. Notably, varieties showing high smut resistance in the field exhibited high susceptibility when inoculated with the plantlet soaking method, suggesting that the plantlet soaking method is a good complement to the traditional methods for screening germplasms with internal resistance. In addition, this method could also be used to monitor the variation of cellular virulence of the smut pathogen strains in the field.